DUF3669, a “domain of unknown function” within ZNF746 and ZNF777, oligomerizes and contributes to transcriptional repression - Al Chiblak, Mohannad (BMC Mol Cell Biol, 2019)
BACKGROUND: ZNF746 and ZNF777 belong to a subset of the large Krüppel-associated box (KRAB) zinc finger (ZNF) transcription factor family. They contain, like four other members in human, an additional conserved domain, the “domain of unknown function 3669” (DUF3669). Previous work on members of this subfamily suggested involvement in transcriptional regulation and aberrant ZNF746 overexpression leads to neuronal cell death in Parkinson’s disease. RESULTS: Here we demonstrate that N-terminal protein segments of the ZNF746a major isoform and ZNF777 act in concert to exert moderate transcriptional repression activities. Full potency depended on the intact configuration consisting of DUF3669, a variant KRAB domain and adjacent sequences. While DUF3669 contributes an intrinsic weak inhibitory activity, the isolated KRAB-AB domains did not repress. Importantly, DUF3669 provides a novel protein-protein interaction interface and mediates direct physical interaction between the members of the subfamily in oligomers. The ZNF746 protein segment encoded by exons 5 and 6 boosted repressor potency, potentially due to the presence of an acceptor lysine for sumoylation at K189. Repressor activity of the potent canonical ZNF10 KRAB domain was not augmented by heterologous transfer of DUF3669, pointing to the importance of context for DUF3669’s impact on transcription. Neither ZNF746a nor ZNF777 protein segments stably associated with TRIM28 within cells. Isoform ZNF746b that contains, unlike the major isoform, a full-length KRAB-A subdomain, displayed substantially increased repressor potency. This increase is due to canonical mechanisms known for KRAB domains since it did not take place in HAP1 knockout models of TRIM28 and SETDB1. A glycine to glutamic acid replacement that complies with a bona fide conserved “MLE” sequence within KRAB-A led to a further strong gain in repressor potency to levels comparable to those of the canonical ZNF10 KRAB domain. Each gain of repressive activity was accompanied by an enhanced interaction with TRIM28 protein. CONCLUSION: DUF3669 adds a protein-protein interaction surface to a subgroup of KRAB-ZNF proteins within an N-terminal configuration with variant KRAB and adjacent sequences likely regulated by sumoylation. DUF3669 contributes to transcriptional repression strength and its homo- and hetero-oligomerization characteristics probably extended the regulatory repertoire of KRAB-ZNF transcription factors during amniote evolution.